Reenvisioning ELT through an English as an International Language’s Lens: Indonesian-Thai Pre-Service English Teachers’ Voices - Purba, Hilarius Raditya Priambada; Kaur, Bal Janatte Raj; Pratiwi, Theodesia Lady; Murillo, Filmor J.; Prasodjo, Pandu Prasodjo (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
This study revisits the perceptions of pre-service English teachers (PSETs) in Indonesia and Thailand on English as an International Language (EIL) concept. This topic under-study scrutinizes their beliefs about the EIL development and implementation, their exposure to diverse English varieties, and the cultural factors that influence their teaching approaches. Review of related literature and studies shows that there has been lack of comparative analysis between non-English-speaking countries regarding Indonesian dan Thai PSETs perception of EIL. This study, therefore, comprises the factors support and hinder the practice of English as an International Language (EIL) in Indonesia and Thailand and the PSETs in Indonesia and Thailand perceive the practice of English as an International Language (EIL) as the focuses understudy.This paper employs a qualitative research method comprised of interviews and observations to study the perspectives of the PSETs under-study. However, generalization of the phenomena will not be attempted as the limitation of the respondents for this study attempts the in-depth analysis of the perceived value on EIL teaching in Indonesia and Thailand. The study pursues a view PSETs as to convey the initial overview and comparison between two countries respecting the EIL practices. This study focuses on 4 (four) PSETs from state high schools in Indonesia and Thailand. The study presents that while teachers acknowledge the global ownership of English, native-speaker norms still dominate assessment standards and curriculum design. Exposure to different English accents is recognized as beneficial, but challenges such as cultural resistance, resource limitations, and lack of real-life practice hinder effective EIL implementation. The findings suggest that systemic changes are needed in curriculum design, teacher training, and assessment methods to align with EIL principles. Future research should explore the long-term impact of EIL-based pedagogy and policy adaptations in non-English-speaking countries so that the practices can be positively beneficial for the implementation of EFL teaching in the context of non-native English-speaking countries.